Meaning of life: An analysis of adolescents' perspectives broken home living with grandparents - Fani Aturohma; Intan Islamia; Nugroho Arief Setiawan (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2025)
The meaning of life among adolescents from broken-home families has received limited attention, especially those living with their grandparents, which presents unique challenges and opportunities for personal growth. This study explores the meaning of life among adolescents from broken-home families living with their grandparents. Through a qualitative approach with descriptive methods, the research investigates the experiences of adolescents in finding meaning in their lives. Data was collected through in-depth interviews and observations in OKU Timur and Bandar Lampung. The study involved early and late adolescents aged 12-21 years who live with their grandparents due to parental divorce or absence. The research identified several factors influencing the meaning of life, including personal understanding, positive actions, relationship building, tri-value experiences, and religiosity. The findings reveal that adolescents develop various strategies to find meaning such as (1) building resilience, (2) adapting to change, (3) a sense of responsibility, (4) seeking social support, (5) strengthening spirituality, and (6) independence. They view life as a learning process, a struggle for independence, and an opportunity to make their grandparents happy. Despite facing challenges, they strive to maintain a positive attitude and focus on what they can control. Religiosity and religious beliefs are their primary source of strength. This study highlights the importance of emotional and spiritual support in helping adolescents overcome life's difficulties and build a positive, meaningful life.